Ways of development of Kazakh-Persian literary connections - Сaдықовa Р. К.; Жaнсеркеевa Э (Journal of Oriental Studies, 2018)
Summary: Iran and Turan is one of the most important and widely discussed topics in the study of historical ,cultural and literary relations between the people of Iran and Turkic. In this article, the beginning of a literary -cultural ties between Iran and Kazakhstan and evidence of two countries, linking books of Avesta and Sabima have been made in recent years and were taken important work on strenghening cultural ties between two countries.During the years of independence our country was expanding and began to admit the scope of literary and cltural relations between Kazakhstan and Iran.All detailed information on the work done in the field of literature of two countries, including numerous studies of the Kazakhstan scientists.